'That doesn't translate': the role of evidence‐based practice in disempowering speech pathologists in acute aphasia management. Issue 4 (4th February 2015) - Foster, Abby; Worrall, Linda; Rose, Miranda; O'Halloran, Robyn
Abstract Background An evidence–practice gap has been identified in current acute aphasia management practice, with the provision of services to people with aphasia in the acute hospital widely considered in the literature to be inconsistent with best‐practice recommendations. The reasons for this evidence–practice gap are unclear; however, speech pathologists practising in this setting have articulated a sense of dissonance regarding their limited service provision to this population. A clearer understanding of why this evidence–practice gap exists is essential in order to support and promote evidence‐based approaches to the care of people with aphasia in acute care settings. Aims To provide an understanding of speech pathologists' conceptualization of evidence‐based practice for acute post‐stroke aphasia, and its implementation. Methods & Procedures This study adopted a phenomenological approach, underpinned by a social constructivist paradigm. In‐depth interviews were conducted with 14 Australian speech pathologists, recruited using a purposive sampling technique. An inductive thematic analysis of the data was undertaken. Outcomes & Results A single, overarching theme emerged from the data. Speech pathologists demonstrated a sense of disempowerment as a result of their relationship with evidence‐based practice for acute aphasia management. Three subthemes contributed to this theme. The first described a restricted conceptualization of evidence‐based practice. The second revealed speech pathologists' strained relationships with the research literature. The third elucidated a sense of professional unease over their perceived inability to enact evidence‐based clinical recommendations, despite their desire to do so. Conclusions & Implications Speech pathologists identified a current knowledge–practice gap in their management of aphasia in acute hospital settings. Speech pathologists place significant emphasis on the research evidence; however, their engagement with the research is limited, in part because it is perceived to lack clinical utility. A sense of professional dissonance arises from the conflict between a desire to provide best practice and the perceived barriers to implementing evidence‐based recommendations clinically, resulting in evidence‐based practice becoming a disempowering concept for some.